1993
DOI: 10.1063/1.109924
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of silicon nanostructures with a scanning tunneling microscope

Abstract: A technique is presented for fabricating Si nanostructures with a scanning tunneling microscope operated in air. The process involves the direct chemical modification of a H-passivated Si(100) surface and a subsequent liquid etch. The chemically modified portions of the surface can withstand a deep (≳100 nm) liquid etch of the unmodified regions with no etch degradation of the modified surface. At a write speed of 1–10 μm/s, large-area (50 μm×50 μm) patterns with lateral feature sizes ∼25 nm are reliably fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(75 citation statements)
references
References 9 publications
0
75
0
Order By: Relevance
“…The creation of reactive surface sites by direct photodesorption may be used for further selective growth or reaction. This scheme has been demonstrated in previous STM writing experiments [31,32]. While patterning by laser induced local heating [33] or hot carrier mediated excitations is limited by the scale of thermal or carrier diffusion, the direct photodesorption mechanism can provide much better selectivity and spatial resolution.…”
mentioning
confidence: 85%
“…The creation of reactive surface sites by direct photodesorption may be used for further selective growth or reaction. This scheme has been demonstrated in previous STM writing experiments [31,32]. While patterning by laser induced local heating [33] or hot carrier mediated excitations is limited by the scale of thermal or carrier diffusion, the direct photodesorption mechanism can provide much better selectivity and spatial resolution.…”
mentioning
confidence: 85%
“…These oxide patterns have been used for a variety of purposes that include etch masks [3], templates for metalization [4] and insulating layers used to pattern thin metal films [5]. With the aid of in situ electrical measurements this last process can be used to fabricate sub-10 nm metal/oxide devices with precisely controlled electrical properties [6].…”
Section: Introductionmentioning
confidence: 99%
“…Sugimura's group produced local oxidation at both polarities [5], observing that the oxidation rate was higher at positive sample bias (anodization). In addition, breakthroughs towards the practical application of the technique were introduced in 1993 by Day and Allee [6], who used AFM with a metallized tip instead of STM to oxidize silicon surfaces locally, and by Snow et al [7], who locally oxidized H-passivated silicon surfaces using AFM. Other relevant results that should be mentioned are those of Fay et al [8], who demonstrated that the STM-oxidized regions appear as depressed areas when imaged with STM but as raised areas when imaged with AFM, and the dependence of the oxidation on the air humidity as * Corresponding author found by several authors [9].…”
mentioning
confidence: 99%